2009
DOI: 10.1002/gps.2382
|View full text |Cite
|
Sign up to set email alerts
|

Identifying functional impairment with scores from the repeatable battery for the assessment of neuropsychological status (RBANS)

Abstract: The RBANS may be an indicator of functional impairment as well as a neuropsychological testing tool. The use of the RBANS could reduce the amount of testing that is administered to the patient, or can provide a way to compare other measurements of functional impairment to assess accuracy of findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 28 publications
4
18
1
Order By: Relevance
“…With the addition of the Visuospatial Constructional Index found by Duff's group, these findings supported those reported by Randolph et al (1998). In addition to demarcating AD from normal-aged elderly individuals, Hobson, Hall, Humphreys-Clark, Schrimsher, & O'Bryant (2010) reported that many of the RBANS indexes and subtests were associated with domains on the Clinical Dementia Rating Scale (Hughes, Berg, Danziger, Coben, & Martin, 1982), suggesting that the RBANS can predict functional impairment in AD.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…With the addition of the Visuospatial Constructional Index found by Duff's group, these findings supported those reported by Randolph et al (1998). In addition to demarcating AD from normal-aged elderly individuals, Hobson, Hall, Humphreys-Clark, Schrimsher, & O'Bryant (2010) reported that many of the RBANS indexes and subtests were associated with domains on the Clinical Dementia Rating Scale (Hughes, Berg, Danziger, Coben, & Martin, 1982), suggesting that the RBANS can predict functional impairment in AD.…”
Section: Introductionsupporting
confidence: 67%
“…Third, this study focused solely on neuropsychological test performance and did not take into account patient or caregiver report of functional dependence or independence (i.e., activities of daily living [ADLs], instrumental activities of daily living [IADLs]). The findings by Hobson et al (2010) suggest that investigation of ADLs and IADLs through patient and=or caregiver report is a worthwhile endeavor as these reports may serve to enhance diagnostic accuracy when combined with cognitive performance. Fourth, the sample sizes of the study groups, most notably the AD group, were relatively small and may potentially limit the generalizability of the study findings.…”
Section: Discussionmentioning
confidence: 91%
“…These scores were approximately 1.5 SD below the age-adjusted population mean of 100±15 and were similar to scores for patients with mild cognitive impairment. 29 At 3 months, 40% of the patients had global cognition scores that were worse than those typically seen in patients with moderate traumatic brain injury, 30 and 26% had scores 2 SD below the population means, which were similar to scores for patients with mild Alzheimer's disease (Fig. 1).…”
Section: Prevalence and Severity Of Long-term Cognitive Impairmentmentioning
confidence: 63%
“…Freilich and Hyer [6] found that, in 66 patients with dementia, the RBANS Attention, Visuospatial/Constructional and Immediate Memory indices were significantly correlated with both basic and instrumental activities of daily living. Hobson et al [7] found that the RBANS Language Index score was significantly related to the clinical dementia rating (CDR) scale [8] domain scores of community affairs, home and hobbies, personal care, memory and judgement in patients with AD and with mild cognitive impairment. In addition, the RBANS Immediate Memory Index scores were significantly related to the CDR memory, judgement and problem-solving domains.…”
Section: Introductionmentioning
confidence: 99%